Analisis Efisiensi Teknis Usaha Tani Padi Sawah di Desa Boronubaen Kecamatan Biboki Utara Kabupaten Timor Tengah Utara - Fransiska X.Timo; Mardit N Nalle; Dira A.Pramitha (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2024)
This research aims to analyze what factors influence lowland rice production in Boronubaen Village, North Biboki District, North Central Timor Regency and to analyze the efficiency value of lowland rice production in Boronubaen Village, North Biboki District, North Central Timor Regency. The research and sampling method in this research is purposive sampling. This research will be carried out in Boronubaen Village, North Biboki District, North Central Timor Regency from June until the end of 2022. The number of samples taken in this research is 73 farmers in farmer groups. The research results show that the factors that influence lowland rice production are seeds, Klensec, Ben Subur and Urea, while land area, NPK, labor have no effect on lowland rice production in Boronobaen Village, North Biboki District, TTU Regency and that the efficiency value in the research This is 0.95, meaning that technically rice farming in Boronobaen Village is efficient